2021
DOI: 10.1007/s00029-020-00614-1
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Lagrangians in toric del-Pezzo surfaces

Abstract: We look at how one can construct from the data of a dimer model a Lagrangian submanifold in $$(\mathbb {C}^*)^n$$ ( C ∗ ) n whose valuation projection approximates a tropical hypersurface. Each face of the di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Example 4.2.2 (Lagrangian pair of pants). In [Mat18], it was shown that the tropical pair of pants centered at the origin was an exact Lagrangian submanifold; a similar proof was given in [Hic21b] which showed that all tropical Lagrangian submanifolds constructed from the data of a dimer are exact.…”
Section: Geometric Lagrangians Versus Lagrangian Branesmentioning
confidence: 78%
See 1 more Smart Citation
“…Example 4.2.2 (Lagrangian pair of pants). In [Mat18], it was shown that the tropical pair of pants centered at the origin was an exact Lagrangian submanifold; a similar proof was given in [Hic21b] which showed that all tropical Lagrangian submanifolds constructed from the data of a dimer are exact.…”
Section: Geometric Lagrangians Versus Lagrangian Branesmentioning
confidence: 78%
“…It is possible for non-regular Maslov index 0 disks to appear with boundary on L ε V , even in simple examples (see example 4.2.11). More generally, [Hic21b] shows that there exists a "wall-crossing" phenomenon which occurs for isotopies between tropical Lagrangian submanifolds, and that the count of these Maslov index 0 holomorphic disks play a crucial role in understanding coordinates on the moduli space of tropical Lagrangian submanifolds.…”
Section: Geometric Lagrangians Versus Lagrangian Branesmentioning
confidence: 99%
“…In recent years, a variation in the form of toric hyperplane arrangements has been studied more prominently, from combinatorial, algebraic, and topological point of views; see [2,3] for examples. Some applications of the theory of toric hyperplane arrangements to toric varieties have been presented in [4,5].…”
Section: Introduction 1hyperplane Arrangementsmentioning
confidence: 99%
“…[4]). Also, all tropical curves of genus ≤ 2 can be lifted to an exact Lagrangian submanifold of (C * ) 2 , as described in [8].…”
Section: Introductionmentioning
confidence: 99%